Kewirausahaan Untuk Meningkatkan Produk “Sitake”: Pengembangan OVOP di Desa Kertamekar Tanjungkerta Sumedang - Zulganef (Bandung Conference Series: Economics Studies, 2024)
Abstract. This article discusses the efforts to develop One Village One Product (OVOP) in Kertamekar Village, Tanjungkerta District, Sumedang Regency. The superior product is SITAKE, which stands for Cassava Talas Keju, which is a chip product made from cassava. The community service team went directly to the village community to dig deeper and provide assistance through the concept of entrepreneurship. One of the activities is a seminar with the theme of developing creative ideas in business. Kertamekar Village has quite extensive rice fields and agricultural land. According to badan Pusat Statistik (BPS) in 2014, Kertamekar Village has the status of a rural village with a classification as a self-sufficient village. The community service team also made other efforts to support village economic development and community empowerment. Among other things, by reactivating the youth Posyandu to help develop stunting prevention activities and providing additional food to stunted toddlers and pregnant women. Abstrak. Artikel ini membahas mengenai upaya pengembangan One Village One Product (OVOP) di Desa Kertamekar Kecamatan Tanjungkerta Kabupaten Sumedang. Produk unggulannya adalah SITAKE yaitu singkatan dari Singkong Talas Keju, yang merupakan produk keripik terbuat dari singkong. Tim pengabdian masyarakat terjun langsung ke masyarakat desa menggali lebih dalam dan memberikan pendampingan melalui konsep kewirausahaan. Salah satu kegiatannya berupa seminar dengan tema pengembangan ide kreatif dalam bisnis. Desa Kertamekar memiliki lahan persawahan dan pertanian yang cukup luas. Menurut Badan Pusat Statistik (BPS) pada tahun 2014, Desa Kertamekar memiliki status sebagai pedesaan dengan klasifikasi sebagai desa swasembada. Tim pengabdian juga melakukan upaya lain untuk mendukung pengembangan ekonomi desa dan pemberdayaan masyarakat. Antara lain dengan mengaktifkan Kembali posyandu remaja untuk membantu mengembangkan kegiatan pencegahan stunting dan pemberian makanan tambahan kepada para balita stunting dan ibu hamil.